The Relationship Between Intra-Group Status and Propensity for Conformity in the Process of Forming Group Norms - Pavlenko, Valentina (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2023)
The question of the relationship between the intragroup status of a group member and the degree of his conformity remains unresolved. Proponents of the idea of "middle-status conformity" tend to view low-status members as weakly susceptible to social influence, while their opponents - the most conforming part of the group. An experimental study of this problem became the purpose of this article. 74 students of the 4th senior (8-11) grades took part in it. The following methods were used: a specially designed experiment to study the process of formation of group norms, sociometry and referentometry. The obtained results did not confirm the idea of middle status conformity. At the same time, the hypothesis of the existence of a significant negative relationship between intragroup status and susceptibility to group influence was confirmed. Leaders are characterized by stability of opinion and immutability of position, while low-status members are characterized by pronounced fluctuations in assessments and opinions. It is shown that with age, the revealed relationship between in-group status and the degree of susceptibility to social influence increases. The conclusions drawn are limited to natural, long-established and well-structured groups; physical characteristics in a situation of uncertainty as an object of assessment; definition of intragroup status as a combination of sociometric status with referentiality; conforming behavior in the form of internalization.